2011
DOI: 10.2337/db11-0314
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant Accumulation of Undifferentiated Myeloid Cells in the Adipose Tissue of CCR2-Deficient Mice Delays Improvements in Insulin Sensitivity

Abstract: OBJECTIVEMice with CCR2 deficiency are protected from insulin resistance but only after long periods of high-fat diet (HFD) feeding, despite the virtual absence of circulating inflammatory monocytes. We performed a time course study in mice with hematopoietic and global CCR2 deficiency to determine adipose tissue–specific mechanisms for the delayed impact of CCR2 deficiency on insulin resistance.RESEARCH DESIGN AND METHODSMice with global or hematopoietic CCR2 deficiency (CCR2−/− and BM-CCR2−/−, respectively) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 34 publications
10
47
0
Order By: Relevance
“…It must be acknowledged however, that a parasitic infection most certainly modulates a number of other immune cells, and it is unknown how propolis influences other immune processes; for this reason, it is not possible to by guest, on www.jlr.org Downloaded from say the increased eosinophils are definitively responsible for the improved glucose tolerance in such models as they were non-specific modulations of eosinophils. In our own studies, we found that despite specifically elevating numbers of WAT eosinophils in obese mice with either recombinant IL-5 (rIL-5) treatment or using CCR2 deficient mice, there was no improvement in glucose tolerance [72,110,123]. Several studies have utilized IL-33 to increase ILC2s, eosinophils, and/or M2-like macrophages in WAT, often associated with weight loss and improved glucose control [31,94,106,112,115,117,119].…”
Section: Downloaded Frommentioning
confidence: 99%
“…It must be acknowledged however, that a parasitic infection most certainly modulates a number of other immune cells, and it is unknown how propolis influences other immune processes; for this reason, it is not possible to by guest, on www.jlr.org Downloaded from say the increased eosinophils are definitively responsible for the improved glucose tolerance in such models as they were non-specific modulations of eosinophils. In our own studies, we found that despite specifically elevating numbers of WAT eosinophils in obese mice with either recombinant IL-5 (rIL-5) treatment or using CCR2 deficient mice, there was no improvement in glucose tolerance [72,110,123]. Several studies have utilized IL-33 to increase ILC2s, eosinophils, and/or M2-like macrophages in WAT, often associated with weight loss and improved glucose control [31,94,106,112,115,117,119].…”
Section: Downloaded Frommentioning
confidence: 99%
“…With regard to Ϫ/Ϫ mice after 16 wk of HF feeding were separated based on lean body mass Ͻ23 g (C) and lean body mass Ͼ23 g (D) (n ϭ 11-18 mice/group). the receptor for CCL2, CCR2, most studies have shown a reduction in ATMs (9,19,39). Strikingly though, differences in ATM numbers, inflammation, and insulin sensitivity are not detected until after long periods of HF diet feeding despite a nearly complete absence of circulating inflammatory monocytes.…”
Section: E902 Ccr5 Deficiency In Diet-induced Obese Micementioning
confidence: 99%
“…Kanda et al (13) demonstrated that overexpression of CCL2 increases recruitment of AT macrophages (ATMs), leading to IR. Our group and others have demonstrated that CCR2 Ϫ/Ϫ mice fed a high-fat (HF) diet for a prolonged period of time are partially protected against ATM infiltration, inflammation, and glucose intolerance (9,19,39). Similarly, CXCL5 and its receptor CXCR2 have been shown to reduce ATM content and improve insulin sensitivity in obese mice (8,26,36).…”
mentioning
confidence: 94%
“…Why inflamed adipose tissue is an attractive site for macrophage infiltration is yet unclear. No doubt MCP1 is a chemoattractant for macrophage migration but CCR2 deficient mice have been shown to be protected from HFD-induced insulin resistance and macrophage accumulation 85,86 . Moreover, a few reports indicate that MCP1 is not sufficient for the amount of macrophage that infiltrates during adipose tissue inflammation 87 .…”
Section: Macrophage Participation In Adipose Tissue Inflammation: a Cmentioning
confidence: 99%